1988
DOI: 10.1123/apaq.5.1.60
|View full text |Cite
|
Sign up to set email alerts
|

Blood Flow and Lactic Acid Levels in Exercising Paralyzed Wheelchair Bound Individuals

Abstract: Twenty spinal-cord-injured subjects (4 quadriplegics and 16 paraplegics) were maximally stress tested on the Arizona State University wheelchair ergometer. Physiological data for each individual were collected as follows: (a) blood flow in the left leg by a photoelectric plethysmograph before exercise, during exercise, and postexercise, and (b) blood lactates before exercise and post-exercise. Eleven subjects had increased leg blood flow and vasodilation during exercise, but vasoconstriction postexercise. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…However, other athletes in the present study with spinal cord lesions below T10 demonstrated relatively little change in calf skin temperature. These results support previous observations that large variations in vasomotor responses exist for subjects with lower level spinal cord lesions (Normell 1974;Burkett et al 1988;Gass et al 1988).…”
Section: Lower Body Skin Temperaturessupporting
confidence: 93%
“…However, other athletes in the present study with spinal cord lesions below T10 demonstrated relatively little change in calf skin temperature. These results support previous observations that large variations in vasomotor responses exist for subjects with lower level spinal cord lesions (Normell 1974;Burkett et al 1988;Gass et al 1988).…”
Section: Lower Body Skin Temperaturessupporting
confidence: 93%
“…31 Conclusions: There is level 2 evidence 40,41,52 (reliable results but debatable) showing that local blood volume regulation in denervated limbs is impaired during upper body cycling in SCI. In addition, there is level 2 evidence 40,52,58 (reliable results but debatable) suggesting that leg blood flow increases during upper body cycling; however, these conclusions were not verified statistically. There is however level 2 evidence showing that leg blood flow does not increase to a statically significant level during upper body cycling exercise.…”
Section: Resultsmentioning
confidence: 96%
“…31 58 showed increases in leg blood flow during upper body arm cycling at moderate 40,52 and maximal 58 intensity levels (durations of 4-15 min). The results of Kinzer and Convertino 40 as well as Burkett et al, 58 however, failed to show significant changes, and work by Bidart and Maury 52 did not include a statistical analysis or original data. Hopman et al 31 took this line of research a step further and illustrated that there is no statistically significant increase in femoral artery blood flow during 25 min of upper body cycling.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations